Synthesis and Theoretical Studies of Salicylidene-2,4-diaminophenol - Taleb Rasheed, Rashed (Asian Journal of Chemistry, 2015)
Schiff-base isomers derived from salicylaldehyde and 2,4-diaminophenol has been synthesized and characterized by FTIR and UV-visible spectroscopy. Theoretical calculations of Schiff-base were studied by quantum chemical calculations. The optimized structure of Schiff-base was obtained by density functional theory at B3LYP/6-31G level. Also total energy, heats of formation, dipole moment, point group, molecular orbital’s energy of HOMO and LUMO, energy gaps (Eg) and DG reaction were calculated and here we suggested the better Schiff base structure may be form. According to theoretical study and based on the results of density function theory (DFT), L3 possesses higher stability state compared with other isomers studied.